Rapid detection strategies for the ultra-level chemosensing of uranyl ions. Issue 41 (29th September 2021) - Kumar R, Selva; Venkatesan, Vetriarasu; Bhaskar, R.; Kumar, S. K. Ashok; Sivaramakrishna, Akella; Vijayakrishna, Kari; Brahmmananda Rao, C. V. S.; Sivaraman, N.; Sahoo, Suban K.
Abstract : Developed a new ligand (L ) for the selective detection of UO2 2+ . The sensitivity of L is recognized by LOD and it is as 20 ppb. The smartphone integrated RGB model and testing paper kit are portable tools for the on-site testing applications. Abstract : A simple and reliable colorimetric probe N, N ′-bis-(4-diethylamino-2-hydroxybenzylidene)-1, 10-phenanthroline-2, 9-carbohydrazide (L ) has been synthesised by reacting 4-(diethylamino)salicylaldehyde with 1, 10-phenanthroline-2, 9-dicarbohydrazide. The sensing ability of L was studied by its interactions with various f-block metal ions and other selected metal ions from s- and d-block by colorimetry, UV-visible spectrophotometry, and smartphone integrated red-green-blue (RGB) model in DMSO : H2 O (7 : 3, v/v). The pale-yellow colour of L turns to wine-red upon interaction with uranyl ions (UO2 2+ ) and yellow-orange in the presence of Th 4+, Zr 4+, Fe 3+, and Lu 3+ ions. Other tested metal ions did not show any colour change of L . This color change offered a simple, quick, and consistent method for the selective and sensitive visual detection of trace levels of UO2 2+ ions without any need for sophisticated instruments. Sensor L exhibits two absorption bands at 358 and 389 nm due to ligand-to-ligand charge transfer (LLCT). Upon interaction of L with UO2 2+ and Th 4+ ions, absorption bands are exhibited at 480 nm and 422 nm, respectively, due to ligand-to-metal charge transfer (LMCT). The UV-vis spectral studies indicated the formation of a 1 : 2 ligand-to-metal complex between L and UO2 2+ with an estimated association constant of 1.0 × 10 4 M −2 . Using L, the concentration of UO2 2+ can be detected as low as 73 nM and 150 nM by spectrophotometry and RGB methods, respectively, without any interference from other tested ions with an RSD < 5% ( n = 3). The binding mechanism was studied by 1 H NMR titration, ESI mass, and FT-IR spectral analysis and was well supported by theoretical results. Overall, sensor L demonstrates promising analytical applicability for the detection of UO2 2+ ions in a semi-aqueous medium.